The only one left : a novel - Sager, Riley (New York : Dutton, 2023)
Now reduced to a schoolyard chant, the Hope family murders shocked the Maine coast one bloody night in 1929. While most people assume seventeen-year-old Lenora was responsible, the police were never able to prove it. Other than her denial after the killings, she has never spoken publicly about that night, nor has she set foot outside Hope's End, the cliffside mansion where the massacre occurred. It's now 1983, and home-health aide Kit McDeere arrives at a decaying Hope's End to care for Lenora after her previous nurse fled in the middle of the night. In her seventies and confined to a wheelchair, Lenora was rendered mute by a series of strokes and can only communicate with Kit by tapping out sentences on an old typewriter. One night, Lenora uses it to make a tantalizing offer--I want to tell you everything...
Keywords: Home health aides -- Fiction; Murder -- Fiction; Families -- Fiction; Maine -- Fiction; Thrillers (Fiction); Psychological fiction